The Administration Of Red Fruit Extract (Pandanus Conoideus Lamk.) To Reduce Menstrual Pain Among Adolescent Girls - Cory Chorajon Situmorang; Ni Nyoman Sri Artina Dewi (Journal of Midwifery, 2020)
Menstrual pain or dysmenorrhea is felt by many young women and this can hinder their activities, including learning tasks at school and at home. Therefore, alternatives to overcome pain are always being developed, one of which in this study is the red fruit extract which is known to contain vitamin E with tocopherol as a substance that can inhibit inflammation. Using a pre- and posttest design, this study was divided into two samples (respondents), namely the intervention group by giving red fruit extract for 3 menstrual cycles and the control group that was without treatment. This study used measuring instrument in form of the observation sheet and a numeric rating scale (NRS) 0-10 for pain scale. Processing and data analysis used the SPSS program through editing, coding, scoring, and tabulating activities. Data were analyzed using univariate analysis and bivariate analysis with independent smaple t-test, Kolmogorov Smirnov and Mann-Whitney. The results obtained were that there was a change in the majority of respondents in the intervention group from the majority of pain in the moderate category to the mild category. These results were significantly different when looking at the results in the control group. Therefore, red fruit extract is recommended to be a useful alternative in reducing menstrual pain.